Listening to women: cooperatives and social and solidarity associations as a support network, a Brazilian example - da Silva Gutierrez Ruiz, Julia [UNESP]; Morais, Leandro Pereira [UNESP] (Universitat de Valencia, 2024)
In Brazil, many women are victims of different forms of domestic violence, which can be physical, psychological, moral, sexual and patrimonial. Women victims of domestic violence tend to look for close people to ask for help to get out of the situation, therefore, an informal support network can be an important tool for women to feel protected and ask for help from public organizations. Given that solidarity economic enterprises (SEE) formed only by women are a space for women to strengthen each other, where they socialize and can create bonds, they can also serve as an informal support network for the women who form them, in addition to fostering their financial autonomy. The objective of this article is to identify whether SEE can be part of a support network for women, from the perspective of the women who form them. To this end, three SEE of women were investigated in the brazilian municipality of Araraquara, which has an important history of social movements and public policies aimed at the social and solidarity economy. From the semi-structured interviews carried out with 11 women from three of these SEE, it was possible to obtain results that explain what happens in the empirical field in relation to the theory, such as that women feel comfortable and trust each other, but at the same time At the same time, they do not identify patrimonial violence as violence.
Escuchando las mujeres: cooperativas y asociaciones sociales y solidarias como red de apoyo, un ejemplo brasileño
Keywords: Economía social y solidaria; Gender; Género; Property Violence; Red de Apoyo; Social and Solidarity Economy; Support Network; Violencia Patrimonial